Effect of a hyperbolide mastication apparatus for the treatment of severe sleep bruxism in a child with cerebral palsy: Long-term follow-up - Giannasi, Lilian Chrystiane; Freitas Batista, Sandra Regina; Matsui, Miriam Yumi; Hardt, Camila Teixeira; Gomes, Carla Paes; Oliveira Amorim, Jose Benedito; Oliveira, Claudia Santos; de Oliveira, Luis Vicente Franco; Gomes, Monica Fernandes (Elsevier, 2013)
Purpose: Sleep bruxism is common among the various oromotor alterations found in individuals with cerebral palsy (CP). Few studies have investigated the use of the mastication device denominated hyperbola (HB) and none was found describing the use of such a device for the treatment of bruxism in children with CP. The aim of the present study was to evaluate the effect of the HB on electromyographic (EMG) activity in the jaw-closing muscles and the reduction in sleep bruxism in a child with CP using surface EMG analysis before and after nine months of treatment. Methods: A seven-year-old boy with severe spastic CP and sleep bruxism was enrolled in this study. The HB was chosen as the treatment option for sleep bruxism in this case because the child did not accept an occlusal splint. The HB has a hyperbolic shape and is made of soft, non-toxic, odorless, tasteless silicone. There are five different sizes of HB manufactured based on the diversity of tooth sizes. This device produces proprioceptive excitation in the dentoalveolar nerve, spindles and Golgi tendon organs. HB has been employed for the treatment of temporomandibular disorder, abnormal oro-dental development, abnormal occlusion, xerostomy, halitosis and bruxism. HB therapy was performed for 5 min six times a day over a nine-week period. Surface EMG of the mandible at rest and during maximum contraction was performed on the masseter and temporalis muscles bilaterally to evaluate electromyographic activity before and after nine months of HB usage. Results: HB usage led to a visible tendency toward the reorganization of mastication dynamics, achieving a marked balance in electromyographic activity of the jaw-closing muscles and improving the child's quality of life. Conclusion: Based on the findings of the present study, this noninvasive therapy may be useful for individuals with cerebral palsy due to its positive effects and low cost, which allows its use in the public health realm. Further clinical studies with a larger sample size are needed to validate these results and allow the development of a new treatment protocol for patients with spastic cerebral palsy. © 2013 Elsevier Ltd. All rights reserved.
Keywords: Cerebral palsy; Dentistry; Electromyography; Hyperbola; Sleep bruxism; Therapy